What is Your “Phytolith Load”? An Examination of the Potential for Cross-Contamination During Phytolith Extraction - Buffington, Abigail Francesca; Weiland, Andrew; Arnold, Julia; Arbogast, Drew (Ethnobiology Letters, 2018)
Phytoliths—amorphous opal silica bodies that form in living plant tissues—are assumed to be stable components of a soil matrix, minimally impacted by normal physical forces. This stability enables archaeologists to access an archive of prior vegetative landscapes when discrete horizons are recovered. However, there is a small chance of phytoliths moving in a laboratory setting via aeolian forces, especially after they have been isolated from other materials such as clay, organics, and carbonates, and when multiple samples are being processed simultaneously. As a result, an assessment of contamination risk on sample extraction is necessary for interpreting the results of phytolith analyses. We designed a study to test the potential for contamination on slides in two different locations of the phytolith laboratory. The results of our study inform how we can improve on phytolith processing protocols and analyses to reduce the potential effect of cross-contamination between samples.